2018
DOI: 10.1103/physrevd.97.094021
|View full text |Cite
|
Sign up to set email alerts
|

How classical gluon fields generate odd azimuthal harmonics for the two-gluon correlation function in high-energy collisions

Abstract: We show that, in the saturation/color glass condensate framework, odd azimuthal harmonics of the twogluon correlation function with a long-range separation in rapidity are generated by the higher-order saturation corrections in the interactions with the projectile and the target. At the very least, the odd harmonics require three scatterings in the projectile and three scatterings in the target. We derive the leading-order expression for the two-gluon production cross section which generates odd harmonics: the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
39
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 106 publications
0
39
0
Order By: Relevance
“…Indeed, as shown explicitly recently [15][16][17], the first nontrivial ρ p k 2 ⊥,p correction breaks the accidental parity symmetry and gives a finite contribution to v 3 . Thus a nonzero value for odd azimuthal anisotropies in the CGC EFT can be understood to be a unique signature of the emerging coherence of the classical gluon field in the projectile.…”
mentioning
confidence: 61%
“…Indeed, as shown explicitly recently [15][16][17], the first nontrivial ρ p k 2 ⊥,p correction breaks the accidental parity symmetry and gives a finite contribution to v 3 . Thus a nonzero value for odd azimuthal anisotropies in the CGC EFT can be understood to be a unique signature of the emerging coherence of the classical gluon field in the projectile.…”
mentioning
confidence: 61%
“…One of those data shows sizable azimuthal anisotropy in final hadron distributions [8][9][10][11][12][13][14], which can be interpreted as a result of the hydrodynamic response of the QGP medium to the initial collision geometry [15][16][17][18][19][20][21][22]. Although this has been discussed actively from relativistic hydrodynamics, another interpretation is brought about also by the color glass condensate picture, which gives long-range correlation in rapidity in small colliding systems without invoking the QGP formation [23][24][25][26][27][28][29][30][31][32][33][34][35][36]. Thus the origin of collectivity observed in small colliding system still remains to be understood.…”
Section: Introductionmentioning
confidence: 99%
“…8-a). For example σ CD 0 takes the form (29) where γ denotes the dipole amplitude at Y = Y 0 , and we assumed that exp 1 2 ∆Y ≫ 1. We need to find the scattering amplitude with one cut Pomeron, which is equal to…”
Section: B Healing the Finkelstein -Kajantie Diseasementioning
confidence: 99%
“…Several efforts to calculate corrections to the leading order CGC/saturation approach have been made (see Refs. [19,26,29] which demonstrated that this correction violates the symmetry which lead to a v n for odd n. If these corrections originate from the next-to-leading order corrections, they should have a parametrically strong suppression, while experimentally v 3 < v 2 but v 3 ≈ v 4 . If we believe that the CGC/saturation approach in leading order describes all other physical observables, then we interpret the experimental results, as an indication that the suppression of v 3 is of a numerical nature.…”
mentioning
confidence: 92%